1989
DOI: 10.1115/1.3262257
|View full text |Cite
|
Sign up to set email alerts
|

Laser Velocimeter Measurements in a Centrifugal Flow Pump

Abstract: A laser velocimeter was used to measure velocities within the impeller and volute of a centrifugal pump. Measurements were made at four circumferential and eight radial positions. Flow rates ranged from 40 to 105 percent of design flow. Blade-to-blade profiles for the four circumferential positions indicate the flow is circumferentially asymmetric around the pump even at the design flow. Blade-to-blade profiles show normal blade loading for 90 percent of the impeller, with reverse and zero loading occurring in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 11 publications
2
31
0
1
Order By: Relevance
“…On the contrary, measurements by Miner et al (1989) showed incipient recirculation in the single volute at design flow in the proximity of the tongue, and extensive recirculation for 40% design flow at window 6.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…On the contrary, measurements by Miner et al (1989) showed incipient recirculation in the single volute at design flow in the proximity of the tongue, and extensive recirculation for 40% design flow at window 6.…”
Section: Discussionmentioning
confidence: 94%
“…First, the flow was assumed to be uniform over eight equal sized sectors (defined as Distribution 1). Second, experimental investigations, such as those performed by Brownell and Flack (1984) and Miner et al (1989), are indicative of narrower regions of recirculation in the proximity of the tongue. Because the influence of the cutwaters is localized and less than 1/8 of the exit flow area is affected, each of the sectors near the cutwaters were considered to encompass only 1/16 of the area, which is consistent with the observations of Brownell and Flack and Miner et al, while 'the adjacent sectors were considered as 5/32 of the area (Distribution 2).…”
Section: Mass Flow Ratementioning
confidence: 99%
See 2 more Smart Citations
“…A number of authors have treated this kind of problem like Miner et al [1] for the case of volute. Liu et al [2], Inoue and Cumpsty [3], and Arndt et al [4] have been concerned with the influence of vaned diffuser.…”
Section: Introductionmentioning
confidence: 99%